Association of Single Nucleotide Polymorphisms in Vascular Endothelial Growth Factor with Recurrent Pregnancy Loss in Erbil Province: A Molecular Investigation - Avan Najmadeen Ahmad; Mustafa Saber Al-Attar (Zanco Journal of Pure and Applied Sciences, 2026)
Recurrent pregnancy loss (RPL) is defined as two or more failed pregnancies before 20 weeks of gestation. Genetic polymorphisms, especially alterations in the vascular endothelial growth factor (VEGF) gene, may increase the risk of pregnancy loss. This study aimed to investigate the connection between changes in the VEGF-A gene (-460C/T, -1190A/G, and -1154A/G) and RPL in women from the Erbil Province. The study included 60 women with a history of RPL and 30 healthy women with no history of miscarriage. Genomic DNA was isolated from whole blood samples. The VEGF-A promoter region was amplified using Touchdown PCR, and the resulting PCR products were analyzed by agarose gel electrophoresis and then processed for Sanger sequencing. Statistical analysis was performed using Yates-corrected χ² tests or Fisher's exact tests for small sample sizes. The results demonstrated that the -460 TT genotype was markedly more prevalent in RPL patients than in controls, increasing the risk by 3.3 times. The -460T allele significantly increased the probability of RPL (OR = 3.3, p = 0.0025, 95% CI: 1.49–7.29). For the -1190A/G polymorphism, the homozygous GG genotype was more prevalent in RPL cases, and the -1190G allele was associated with an increased risk (OR = 2.64, p = 0.0138, 95% CI: 1.26–5.52), identifying it as the risk allele for this SNP. In contrast, the -1154A/G polymorphism showed no significant differences in either genotype or allele frequencies between RPL cases and controls (p > 0.05). These findings suggest that some genotypic alterations, notably -460 TT and -1190 GG, may act as genetic risk factors for RPL.